Kegiatan Pemberdayaan Masyarakat di Wilayah Perumahan Batara RW 13, Kelurahan Kahuripan Kecamatan Tawang, Kota Tasikmalaya Tahun 2024 - Fathiah Qolbu; Rifa Ajrina Faisal; Ultanika Indraswarni Anwar; Januar Nur Ismail Nugraha; Andy Muharry (Lembaga Pengembangan Kinerja Dosen, 2024)
Hypertension is one of the leading non-communicable diseases causing global mortality, particularly in low- and middle-income countries. The elderly, as a group vulnerable to hypertension, often lack access to education and motivation to engage in physical activities. This study aims to raise awareness among the elderly about hypertension prevention through physical activity in the form of hypertension exercises and education on the benefits of tomato juice. This research employed a descriptive qualitative method conducted in Perumahan Batara RW 13, Tasikmalaya City, targeting elderly individuals at risk of hypertension.Data were collected through participatory observation and informal interviews, then analyzed based on success indicators. The findings show that this program successfully enhanced community knowledge about hypertension, encouraged active participation in physical activities, and motivated participants to utilize tomato juice as a preventive measure against hypertension. The high enthusiasm of participants during discussions and their willingness to adopt healthy lifestyles indicated the program's success. With improvements in implementation aspects, this program has the potential to be adopted in other regions as a community empowerment strategy to enhance elderly health.